Application of chemometric analysis using physicochemical and chromatographic data to differentiate the origin of plant protection products containing trinexapac-ethyl - Patrycja Marczewska; Joanna Rolnik; Tomasz Stobiecki (Journal of Plant Protection Research)
The European market for plant protection products (PPPs) faces significant challenges related to counterfeit and substandard PPPs, posing threats to sustainable agriculture and food safety. This study explored the application of chemometric methods based on physical, chemical, and technical parameters, as well as data obtained by high-performance liquid chromatography with a diode array detector (HPLC-DAD) and headspace gas chromatography coupled with mass spectrometry (HS-GC/MS), to verify the authenticity of PPPs containing trinexapac-ethyl. A total of 44 formulations were analyzed, including authentic samples and substandard PPPs obtained from various retail points and manufacturers. The developed analytical methods demonstrated robustness in determining physicochemical parameters and generating chromatographic profiles distinguishing between genuine and non-genuine products. Chemometric tools such as principal component analysis (PCA), hierarchical clustering analysis (HCA), and Soft Independent Modeling of Class Analogy (SIMCA) facilitated data interpretation, revealing distinct clusters of samples based on their chemical fingerprints. SIMCA models exhibited their potential for routine quality control assessments. Overall, integrating advanced analytical techniques and chemometrics offers a promising strategy to safeguard the integrity of PPPs, enhance regulatory compliance, and mitigate the risks associated with counterfeit products in the European agricultural market. This approach supports sustainable agricultural practices by ensuring product authenticity and safety, thereby fostering consumer trust and regulatory adherence. In the context of increasing global demand for agricultural products, effective verification of PPPs authenticity becomes a crucial element in ensuring food security, human health, and environmental protection.